The Ledra Palace project: Using emerging technologies to communicate exhibition content - Evaluation of results - Stylianou-Lambert, Theopisti; Heraclidou, Antigone; Ioannou, Christos; Frangoudes, Fotos; Kyriacou, Panayiotis A.; Avraam, Savvas; Neokleous, Kleanthis C.; Avraamides, Marios N. (My University, 2022)
During the past couple of decades, museums resort to using innovative technological solutions in their permanent collections or temporary exhibitions aiming to enhance visitor experience. In the current study, we tested three emerging technologies (i.e., Interactive Book, Interactive Table, Immersive Virtual Reality) that were created to show in a museum exhibition, content related to ‘difficult heritage’ and ‘difficult history’. In a questionnaire administrated at the end of the exhibition, visitors were first asked to evaluate whether the content of the exhibition was better communicated through these interactive technologies than through non-technological (conventional) installations, and then to assess the usability of these technologies. Results revealed that technological installations were as engaging and successful in the presentation and communication of the content of the exhibition as the non-technological installations. Finally, with respect to the usability of the above three technological installations, results were remarkably high (Mdn: 87), with all visitors reporting a clear preference for the immersive virtual reality installation. Studies such as the current one support that interactive technologies should not aim to substitute conventional installations but instead, to complement them to enhance visitor experience and provide alternative
Keywords: Ledra Palace Hotel; emerging technologies; museums